Analysis of Factors Influencing the Use of E-Learning Facilities Among Students in Public Universities in Johor (Research in Management of Technology and Business, 2022)
E-learning facilities are a recognized educational practice. It supports a flexible knowledge acquisition model that can effectively support a larger number of audiences for education and training than traditional education models. The purpose of this study is to identify the factors influencing the use of e-learning facilities among student in public universities in Johor. The factors of influence the use of e-facilities among students that used are technology factors, organization factors and environment factors. Quantitative research methods were used in this study by distributing questionnaires to students from UTHM students and UTM students. The data are analyze using the Statistical Packages for Social Science (SPSS) software. The study used a validated online survey questionnaire to collect the data from 300 valid respondents. The results showed that the main factor influencing the use of elearning among students in public universities in Johor is the technology factors and the least chosen is lecturer factor. In addition, the results show that the platforms that used most by students in public universities in Johor is Google Meet while for the least preferred is Flipgrid. The results of this study are expected to provide valuable insights to institutions and government sector in the educational learning sector.